Neither the Frying Pan nor the Fire: In Search of a Balanced Authentic e-Learning Design through an Educational Design Research Process - Teräs, Hanna; Herrington, Jan (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2014)
Teaching in higher education in the 21st century can be a demanding and complex role and academic educators around the globe are dealing with questions related to change. This paper describes a new type of a professional development program for teaching faculty, using a pedagogical model based on the principles of authentic e-learning. The program was developed with the help of an iterative educational design research process and rapid prototyping based on on-going research and redesign. This paper describes how the findings of the evaluations guided the design process and how the impact of the measures taken was in turn researched, in order to eventually identify and refine design principles for an authentic e-learning program for international teaching faculty professional development.